Optimization of flow impact to detect the defect factor on ball valve - Che Yusof, Nik Syamsul Bahari (2014)
Cavitation is a phenomenon which frequently creates fear within the engineering industry as the violent and critical attacks by cavitation can cause a lot of damage to ball valves. The damage in term of erosion, vibration and noise (e.g. water hammer) is a biggest challenge especially for the valve and pump industry. The energetic bubbles bring very high pressure to implode in a metal surface. The bubbles implosions will consistently digging the surface. Consequently, the failure and damage cannot be avoided. In this research, the aim for the study is to find the best solution to reduce the cavitation attack. The numerical tools embedded inside the simulation software combined with the novel design idea, was applied to enhance the ball valve performance. Moreover, the Pugh method matrix was applied to select the best groove design. The developed groove for ball valve was simulated under same boundary condition with existing experimental and simulation ball valve. The results done by previous researcher for the standard ball valve was compared with results data for develop ball valve. The convincing outcome was obtained, all three develop ball valve produce a better results compare with the standard ball valve. Evidently, in average percentage for energy loss performance error, all develop new design ball valve record the increment percentage of performance starting with D2 (32.96%), followed by D1(30.34%) and D3 (12.38%). In general, the cavitation index average performances for develop new design ball valve performed better than existing standard ball valve. Noticeably, develop design ball valve D2 recorded increasing 46.40% on average performance, this value is the highest increasing performance if compare with D1 model 36.32% and D3 model 34.32%. Thus, the goal to solve the violent cavitation effect was successfully achieved.